P1167SERUM MAGNESIUM IS INVERSELY CORRELATED WITH MEAN PLATELET VOLUME IN PERITONEAL DIALYSIS PATIENTS. (6th June 2020) - Dermitzaki, Eleutheria-Kleio; Giannakopoulos, Panagiotis; Georgoulidou, Anastasia; Tsotsorou, Ourania; Nikolopoulos, Petros; Balafa, Olga; Ntounousi, Evangelia; Stylianou, Kostas; Katsoudas, Spyros; Kyriazis, Periklis; Bacharaki, Dimitra; Vlahakos, Demetrios
Abstract: Background and Aims: Higher Mean Platelet Volume (MPV), as an indicator of larger and hyper-reactive platelets and low serum Mg levels (sMg) have emerged as cardiovascular risk markers, in the general and dialysis population. Magnesium deficiency is linked to platelet hyper-reactivity. Since HypoMagnesemia is common and associated to increased mortality among Peritoneal Dialysis (PD) patients, we aimed to investigate the association of sMg with MVP in PD patients. Method: We studied 95 stable PD patients, 51 men 44 women, with a mean age of 63 ±14 years. Data analyzed included patients demographics, clinical and biochemical data. Univariate and multivariate regression analysis were used to test the associations of variables related to MPV. Results: . The mean platelet (PLT) volume was 9.4 ±1.5 (median: 9.2) fl. The mean platelet (PLT) count was 235 ± 69 (median: 233) [x10 3 μ/L]. The mean sMg was 2.25 ± 0.47 (median: 2.2) mg/dl. MPV was associated positively (p=0.303; p<0.01) with C-reactive protein (CRP) and negatively with sMg (r= -0.246; p<0.05), use of Renin Angiotensin System (RAS) Inhibitors (r=-0.273; p<0.05), PLT count (r=-0.360; p<0.001) and white blood cell (WBC) count (r=-0.254; p<0.05). The results of our multiple regression model (Table) showed that all the above mentioned factors that were included in the model, except WBC, were independent determinants of MPV. Conclusion: Our results show a significant inverse correlation of serum Magnesium with Mean Platelet Volume in Peritoneal Dialysis patients. Given the emerging role of Mg in platelet reactivity, sustaining higher sMg levels, along with minimizing inflammation and using RAS inhibitors may improve cardiovascular outcomes in PD patients via modulation of MPV.